The effect of swimming on overuse injuries in athletes through cross training strategy: A systematic review - Li, J. (Pakistan Journal of Life and Social Sciences, 2024)
One of the major challenges faced by sports medicine is overuse injuries. Cross training helps avoid overuse injuries by minimizing the repeated impact on any one muscle or joint. Swimming is a great cross-training option because it is low-impact and works the entire body. Thus, the current study aims to explore the effect of swimming on overuse injuries in athletes through a cross-training strategy. Subsequently, the research questions include: RQ1: Does swimming help athletes experience fewer overuse injuries as a cross-training exercise? RQ2: What effect can swimming have on athletes recuperating from overuse injuries throughout their rehabilitation? RQ3: What are the physiological and biomechanical advantages of swimming that make it a useful cross-training exercise? The study followed a systematic review of 28 works of literature on related topics. Subsequently, the studies were analyzed through thematic analysis. It was found that swimming would reduce the risk of overuse injuries, aiding in rehabilitation. Secondly, it allowed athletes to stay active during recovery while reducing stress on injured areas, making it an excellent choice for joint and ligament injuries. Third, swimming provides physiological and biomechanical benefits, such as improved cardiovascular efficiency, stroke mechanics, and muscular endurance. The study identified limitations such as publication and language bias. However, future studies might follow the findings of this study to conduct a longitudinal study for investigating the role of swimming as a cross-training.